THE ROLE OF THE HEALTH SERVICE IN HEALTH PROMOTION TO MANAGE STUNTING PREVALENCE IN KERAMAT MUFAKAT VILLAGE, CENTRAL ACEH DISTRICT - Hafizah Nur; Jun Musnadi Is (RADJA PUBLIKA, 2023)
The background of this research is that the number of toddlers affected by cases of malnutrition (stunting) in the village of Keramat Mufakat is as many as 17 toddlers affected by malnutrition (stunting) out of the 100 toddlers, including those in Bebesen District with details of 17 toddlers found in the village of Keramat Mufakat . Research Methods Researchers used a type of qualitative population research and the samples taken were claimed to be informants. The expected informant criteria include: standards of knowledge and standards of behavior towards nutritious food that is far from the risk of stunting. This research was conducted in Keramat Mufakat Village, Bebesen District, Central Aceh District. This research was conducted in the village of Keramat Mufakat, Bebesen sub-district, Central aceh district on September 25, 2022. Research results Based on the results of this study, it was found that most children received exclusive breastfeeding. This is because the majority of mothers have employment status as housewives or do not have a job which can make it difficult for mothers of toddlers to exclusively breastfeed. In addition, there are problems regarding the lack of breastfeeding for mothers, and regarding the problem of income for parents who are unable to meet family needs so that most toddlers are not given or assisted with formula milk, but are only given breast milk and continue until the age of 2 years. Conclusion In the study in the village of Keramat Mufakat there were 17 toddlers who experienced malnutrition (stunting). Significant risk factors for stunting were history of complementary feeding, history of infectious diseases,